Accelerated aging exacerbates a pre‐existing pathology in a tau transgenic mouse model. Issue 2 (4th February 2017) - Bodea, Liviu‐Gabriel; Evans, Harrison Tudor; Van der Jeugd, Ann; Ittner, Lars M.; Delerue, Fabien; Kril, Jillian; Halliday, Glenda; Hodges, John; Kiernan, Mathew C.; Götz, Jürgen
Summary: Age is a critical factor in the prevalence of tauopathies, including Alzheimer's disease. To observe how an aging phenotype interacts with and affects the pathological intracellular accumulation of hyperphosphorylated tau, the tauopathy mouse model pR5 (expressing P301L mutant human tau) was back‐crossed more than ten times onto a senescence‐accelerated SAMP8 background to establish the new strain, SApT. Unlike SAMP8 mice, pR5 mice are characterized by a robust tau pathology particularly in the amygdala and hippocampus. Analysis of age‐matched SApT mice revealed that pathological tau phosphorylation was increased in these brain regions compared to those in the parental pR5 strain. Moreover, as revealed by immunohistochemistry, phosphorylation of critical tau phospho‐epitopes (P‐Ser202/P‐Ser205 and P‐Ser235) was significantly increased in the amygdala of SApT mice in an age‐dependent manner, suggesting an age‐associated effect of tau phosphorylation. Anxiety tests revealed that the older cohort of SApT mice (10 months vs. 8 months) exhibited a behavioural pattern similar to that observed for age‐matched tau transgenic pR5 mice and not the SAMP8 parental mice. Learning and memory, however, appeared to be governed by the accelerated aging background of the SAMP8 strain, as at both ages investigated, SAMP8 and SApT mice showed a decreased learning capacity compared to pR5 mice. We therefore conclude that accelerated aging exacerbates pathological tau phosphorylation, leading to changes in normal behaviour. These findings further suggest that SApT mice may be a useful novel model in which to study the role of a complex geriatric phenotype in tauopathy.